PERAN BHABINKAMTIBMAS DALAM MENCEGAH TINDAK PIDANA PENCURIAN KENDARAAN BERMOTOR DI WILAYAH HUKUM POLSEK JATINANGOR - M. DIAN DZIKRILLAH DZIKRILLAH (Advances in Police Science Research Journal, 2020)
Starting from the problems arise in the Jatinangor which has a fairly higher of urbanization than other regions in the Sumedang. Special attention is needed to this region, related to order and environmental safety in the community so that indigenous people and migrants from the region Jatinangor stay awake. Based on data from the Sumedang Regional Police District, Jatinangor also entered into areas prone to crime, especially crimes Curanmor. Bhabinkamtibmas in performing must active role in society. It is expected that the existence of recommendations and guidelines for the role of Bhabinkamtibmas which is already listed in Perkap No. 3 of 2015 can reduce the occurrence of kamtibmas disruption in the form of Curanmor in Jatinangor. The role of Bhabinkamtibmas Jatinangor police station in this research is known through analysis based on management theory and the role theory and evaluation of the role of Bhabinkamtibmas will be analyzed by swot analysis. This research uses a qualitative research approach and the focus of the research is the role of Bhabinkamtibmas in preventing Curanmor. Data collection techniques through observation, interviews and study documents and data validation using the triangulation method. The location of this research is in the jurisdiction of Jatinangor Sector Police, Sumedang Regional Police. The results of the study indicate the need for intensive attention to the community in relation to prevention of fraud, and an increase in public attention about the environment and work closely with the police to maintain the community environment and order. There are internal and external factors that influence the role of Bhabinkamtibmas in preventing curanmor. Internal factors include the quality of Bhabinkamtibmas personnel. External factors include the quality of society and geographical conditions. Based on the results and findings of the study, suggestions from the authors to the Bhabinkamtibmas Jatinangor police station to harmonize the quality of personnel, be more innovative, pay special attention to vulnerable areas and involve all elements of the community to care for the surrounding environment and order. Keywords: Role of Bhabinkamtibmas, Curanmor, Prevention of Curanmor, Population Density, Jatinangor Sector Police.